Determinants of payment method in cross-border mergers and acquisitions. - Lin, Yujun. (2008)
This paper aims to pioneer the investigation of payment method determinants unique to cross-border Merger and Acquisition transactions. First, we extend the existing literature to a sample of 469 cross-border deals over the period 2001-2005. We find strong evidence that the existing hypotheses still apply in an international context. More importantly, we propose and test additional cross-border considerations in order to generate a better understanding of method of payment motivations specific to international deals. While exchange-rate volatility did not appear to affect the choice of payment method, we find strong evidence that stock payment is more likely when both parties are listed on a common stock exchange. The further application of a stock-market development variable showed that target shareholders consider transaction costs in their decision to accept stock payment from a foreign acquirer. Lastly, we find that acquirers from more liquid stock markets possess stock which is viewed as a more attractive payment method in cross-border transactions.